Exploring Options to Institutionalize the Dzud Disaster Response Product in Mongolia - Lailan, Tungalag (World Bank, Washington, DC, 2013)
This study aims to provide the guiding principles to the government of Mongolia (GOM) towards creating comprehensive ex-ante risk management strategy based on the assessment of the pros and cons of historical approach of livestock risk management as well as best practices around the world. For instance, it proposes an option for the National Disaster Indemnification Program (NDIP) that acts as a state insurance enterprise and provides social insurance protection to herders against extreme dzud disaster events. The report concludes that by introducing NDIP, the GOM would have an opportunity to introduce the social safety net product, publicly provided and financed, to respond quickly to herders most affected by extremely high levels of livestock losses following major dzud event.The NDIP would assist the Government of Mongolia and international donors to structure and distribute dzud related disaster financing in a systematic, timely and transparent manner, while keeping high covariate risks manageable.